2022
DOI: 10.1007/s11368-022-03156-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of organic matter degradation in cohesive sediment: a detailed rheological analysis

Abstract: Purpose The presence of organic matter in cohesive sediment results in the formation of clay-organic flocs, which eventually impart complex rheological behavior including shear-thinning, viscoelasticity, thixotropy and two-step yielding to mud. In this study, the influence of microbial degradation of sediment organic matter on the rheological properties of mud samples, having similar densities, was examined. Materials and methods Mud samples were collected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…The later was supported by Jommi et al (2019) who found that the presence of gas must be accounted for when studying the reduction in shear stresses by organic matter decay. It was found that the SOM decay caused a significant decrease in the rheological properties including yield stress, crossover amplitude, complex modulus, and thixotropic hysteresis area (Shakeel et al 2022). For the given data set, the changes in density during the period of incubation observed in this study were only minor, which means that the detected changes in the rheological behavior are not caused by changes in the material's density.…”
Section: General Effects Of Som Decay On Static and Fluidic Yield Str...mentioning
confidence: 57%
See 3 more Smart Citations
“…The later was supported by Jommi et al (2019) who found that the presence of gas must be accounted for when studying the reduction in shear stresses by organic matter decay. It was found that the SOM decay caused a significant decrease in the rheological properties including yield stress, crossover amplitude, complex modulus, and thixotropic hysteresis area (Shakeel et al 2022). For the given data set, the changes in density during the period of incubation observed in this study were only minor, which means that the detected changes in the rheological behavior are not caused by changes in the material's density.…”
Section: General Effects Of Som Decay On Static and Fluidic Yield Str...mentioning
confidence: 57%
“…In literature, higher yield stress values of fine-grained sediments were typically associated to either higher density or higher organic matter content (Van Kessel and Blom 1998;Soltanpour and Samsami 2011;Xu and Huhe 2016;Shakeel et al 2019Shakeel et al , 2020aShakeel et al , 2022 with organic matter assumed to result in a stronger structure, i.e., higher yield stresses, of fine-grained sediment (Shakeel et al 2019). Shear stresses of long-term incubated (250 days) samples correlated best with long-term SOM degradability, seen in Fig.…”
Section: General Effects Of Som Decay On Static and Fluidic Yield Str...mentioning
confidence: 73%
See 2 more Smart Citations
“…The reduced static and fluidic yield stress of sediments can enhance port maintenance dredging and navigability of ports and waterways. Shakeel et al ( 2022 ) studied the impact of microbial degradation of organic matter on the rheological properties of mud samples by exposing fresh and degraded mud samples collected from three different locations in the Port of Hamburg to various stress tests (stress ramp-up tests, amplitude sweep tests, frequency sweep tests, time dependence tests, and structural recovery tests). They confirmed that degradation of organic matter indeed weakens the strength of mud and found that the strongest degradation occurs after 3 and 150 days.…”
Section: Sediment Assessment and Management – Concepts And Policiesmentioning
confidence: 99%